Ordered SrTiO3 Nanoripples Induced by Focused Ion Beam - Wu, Jiang; Chen, Gang; Zeng, Zhaoquan; Li, Shibin; Xu, Xingliang; Wang, Zhiming M.; Salamo, Gregory J. (Nano-Micro Letters, 2012)
Ordered nanoripples on the niobium-doped SrTiO3 surfaces were fabricated through focused ion beam bombardment. The surface morphology of the SrTiO3 nanoripples was characterized using in situ focused ion beam/scanning electron microscopy. The well-aligned SrTiO3 nanostructures were obtained under optimized ion irradiation conditions. The characteristic wavelength was measured as about 210 nm for different ion beam currents. The relationship between the ion irradiation time and current and SrTiO3 surface morphology was analyzed. The presented method will be an effective supplement for fabrication of SrTiO3 nanostructures that can be used for ferroelectric and electronic applications.